Exploring Digital Proficiency Among Mothers of School-going Children in Kerala: A Comprehensive Analysis - Arya, V S; Sreejith , S; Rekha, Pillai (Journal of Telecommunications and the Digital Economy, 2024)
Early exposure to social and digital media in this digital age greatly influences children’s lives, leading to an increasing number of parents and educators becoming concerned about the potential negative effects of excessive screen time. By investigating mothers’ digital competencies as informal educators, this study fills a significant research gap. The paper emphasises women as mentors, highlighting their responsibility to supervise and guide their children’s use of digital devices in an era of pervasive connectedness. Using a modified version of the DigCompEdu framework, the study focuses on two essential elements: empowering children; and fostering their understanding of digital competence areas. A thousand homemakers from two wards of the Kochi Corporation area in the Ernakulam district, Kerala, India are included in the study. Discriminant analysis is used to identify four important skill areas that demonstrate significant group differences – between Novice, Basic, Independent, and Proficient user groups. Results imply that tailoring digital literacy programs to mothers’ varying proficiency levels can enhance their ability to navigate digital parenting effectively. Additionally, integrating sociodemographic factors into interventions can ensure relevance and efficacy in addressing digital competence disparities among mothers.